2017
DOI: 10.1002/14651858.cd003430.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre for the prevention of recurrent colorectal adenomas and carcinomas

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 113 publications
0
62
0
2
Order By: Relevance
“…Second, some challenged Burkitt's enthusiasm for fibre by pointing to confounding variables such as healthy lifestyle factors including reduced smoking, greater exercise and consumption of nonfibre nutrients found in fruit and vegetables . Third, there were exaggerated expectations for the therapeutic potential of fibre in reversing gastrointestinal pathology . The potential for fibre to prevent rather than treat infectious, diverticular and neoplastic disorders would have been a more realistic objective.…”
Section: Challenges and Disappointmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, some challenged Burkitt's enthusiasm for fibre by pointing to confounding variables such as healthy lifestyle factors including reduced smoking, greater exercise and consumption of nonfibre nutrients found in fruit and vegetables . Third, there were exaggerated expectations for the therapeutic potential of fibre in reversing gastrointestinal pathology . The potential for fibre to prevent rather than treat infectious, diverticular and neoplastic disorders would have been a more realistic objective.…”
Section: Challenges and Disappointmentsmentioning
confidence: 99%
“…However, much of the available prospective data have demonstrated an inverse relationship between fibre intake and incident colorectal cancer risk . The previous discrepancies are likely explained by a lack of evidence for fibre in reducing the risk of recurrent adenomatous colorectal polyps . Proposed mechanisms for a protective fibre effect on colorectal cancer risk include dilution of faecal carcinogens, quicker gut transit times, SCFA production and binding of carcinogenic bile acids .…”
Section: Challenges and Disappointmentsmentioning
confidence: 99%
“…Although the precise effects of diets on oncogenesis have not been completely elucidated, microbiome changes and chronic inflammation are believed to contribute to the development of CRC. Whereas experimental evidence supports the hypothesis that dietary fiber maybe protective against CRC development, epidemiologic data remains inconclusive . Preventative measures, including dietary and lifestyle changes, are an attractive strategy to reduce the incidence of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Butyrate has been reported as a chemo-preventive agent [39,40]. However, a Cochrane review of randomized controlled trials found no statistically significant effect of dietary fiber intervention versus placebo or normal diet on the recurrence of colorectal adenomas [41]. Further research is therefore needed to investigate the potential benefits of fiber for CRC prevention.…”
Section: Discussionmentioning
confidence: 99%